3D geometrical modelling of post-foliation deformations in metamorphic terrains (Syros, Cyclades, Greece). (September 2015) - Philippon, Mélody; Le Carlier de Veslud, Christian; Gueydan, Frédéric; Brun, Jean-Pierre; Caumon, Guillaume
Abstract: Superposed to ductile syn-metamorphic deformations, post-foliation deformations affect metamorphic units during their exhumation. Understanding the role of such deformations in the structuration of metamorphic units is key for understanding the tectonic evolution of convergence zones. We characterize post-foliations deformations using 3D modelling which is a first-order tool to describe complex geological structures, but a challenging task where based only on surface data. We propose a modelling procedure that combines fast draft models (interpolation of orientation data), with more complex ones where the structural context is better understood (implicit modelling), allowing us to build a 3D geometrical model of Syros Island blueschists (Cyclades), based on field data. With our approach, the 3D model is able to capture the complex present-day geometry of the island, mainly controlled by the superposition of three types of post-metamorphic deformations affecting the original metamorphic pile: i) a top-to-South ramp-flat extensional system that dominates the overall island structure, ii) large-scale folding of the metamorphic units associated with ramp-flat extensional system, and iii) steeply-dipping normal faults trending dominantly NNW-SSE and EW. The 3D surfaces produced by this method match outcrop data, are geologically consistent, and provide reasonable estimates of geological structures in poorly constrained areas. Highlights: We investigate post-metamorphic deformation that structures high-pressure units. We developed a method combining extensive fieldwork and 3D geometrical modelling. Our workflow combines interpolation of surface data and implicit in-depth modelling. Our workflow allow to model in three dimensions complex geometrical pattern.